2017
DOI: 10.1111/exd.13164
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Let‐7b inhibits keratinocyte migration in cutaneous wound healing by targeting IGF2BP2

Abstract: Wound healing is a complex process which involves proliferation and migration of keratinocyte for closure of epidermal injuries. A member of microRNA family, let-7b, has been expressed in mammalian skin, but its exact role in keratinocyte migration is still not in knowledge. Here, we showed that let-7b regulates keratinocyte migration by targeting the insulin-like growth factor IGF2BP2. Overexpression of let-7b led to reduced HaCaT cell migration, while knockdown of let-7b resulted in enhanced migration. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Recent study demonstrated that let-7b stimulates differentiation and prevents metaplasia by regulating HNF6 expression in pancreatic acinar cells [ 14 ]. It is also becoming increasingly recognized that let-7b plays an important role in hair growth [ 15 , 16 ], cutaneous wound healing [ 17 ] and skin disease [ 18 ]. Recently, it was found that let-7b inhibits keratinocyte migration through targeting IGF2BP2 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study demonstrated that let-7b stimulates differentiation and prevents metaplasia by regulating HNF6 expression in pancreatic acinar cells [ 14 ]. It is also becoming increasingly recognized that let-7b plays an important role in hair growth [ 15 , 16 ], cutaneous wound healing [ 17 ] and skin disease [ 18 ]. Recently, it was found that let-7b inhibits keratinocyte migration through targeting IGF2BP2 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also becoming increasingly recognized that let-7b plays an important role in hair growth [ 15 , 16 ], cutaneous wound healing [ 17 ] and skin disease [ 18 ]. Recently, it was found that let-7b inhibits keratinocyte migration through targeting IGF2BP2 [ 17 ]. As well as, let-7b has been also implicated in other malignacies e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have shown that miR-142 is required for neutrophils to clear S. aureus infected-skin wound sites (Tanaka et al, 2017). Mice with Let-7b overexpression exhibit a delay in re-epithelialization at skin wound sites (Wu et al, 2017).…”
Section: Wound -Rel Ated Mirna S Are P Otential Targ E Ts For Impromentioning
confidence: 99%
“…miR-126 overexpression has been shown to rescue the diabetes-induced impairment of phagocytosis of apoptotic cardiomyocytes (13). In addition, Let-7b was revealed to inhibit keratinocyte migration in cutaneous wound healing (14). Moreover, reports have described that the topical application of miR-132 mimic mixed with pluronic F-127 gel in chronic wounds promotes reepithelialization (15) and that miR-27b rescues impaired BM-derived angiogenic cell function and improved wound healing in type 2 diabetic mice (16).…”
mentioning
confidence: 99%